Islam beyond conflict Indonesian Islam and Western political theory - Azra, Azyumardi 1955-2022; Hudson, Wayne (Routledge, 2017)
1. Introduction / Azyumardi Azra and Wayne Hudson -- 2. Political modernity and Indonesian Islam : a manifesto / Azyumardi Azra and Wayne Hudson -- 3. Islamic perspectives and the rules of law and constitutionalism / N.A. Fadhil Lubis -- 4. Constitutional values and an Islamic state / Adnan Buyung Nasution -- 5. The ambiguities of the rule of law / Brian Galligan -- 6. Western and Islamic conceptions of the rule of law / Spencer Zifcak -- 7. Democracy and Islam / Bahtiar Effendy -- 8. Islam and democratisation in Indonesia / Ahmad Syafii Maarif -- 9. Islam and the claims of democracy / Graham Maddox -- 10. Democratic leadership / Haig Patapan -- 11. Islamic perspectives on citizenship and statehood / N.A. Fadhil Lubis -- 12. Towards a conceptual framework for citizenship / Geoffrey Stokes -- 13. Liberal and communitarian approaches to citizenship / Janna Thompson -- 14. Problems with citizenship / Barry Hindess -- 15. Religious pluralism in Indonesia / Azyumardi Azra -- 16. Pluralism and liberalism / John Kane -- 17. Pluralism and universalism / George Crowder -- 18. Human rights and duties in Islam / N.A. Fadhil Lubis -- 19. Human rights and pluralism / Joseph Camilleri -- 20. Civil society and tolerance in Indonesia / Saiful Mujani -- 21. Civil society and the media in Indonesia / Philip Kitley -- 22. Indonesian Islam and democracy : ways ahead / Wayne Hudson and Azyumardi Azra
Keywords: Islam and politics / Indonesia; Islamic law / Indonesia; Indonesia / Politics and government; Droit islamique / Indonésie; Indonésie / Politique et gouvernement; Islam and politics; Islamic law; Politics and government; Indonesia / https://id.oclc.org/worldcat/entity/E39PBJcrbVHmQ674B9vYY3X8G3